Silvicultural Systems in the Restoration of Normal Forest: A Review - Ghimire, Alizza; Paudel, Sarmila; Devkota, Abinash (Forestry: Journal of Institute of Forestry, Nepal, 2022)
This paper review show different silvicultural systems help to restore normal forests, their usefulness and limitations. It is based on a desk review of various secondary data. Nature of ownership, management objectives, and site quality determine the silvicultural system to be adopted. In regular (even-aged) forest, normality is carried out by the clear-felling system, uniform shelterwood system and coppice system while irregular (uneven-aged) normal forest is managed using the selection system. As perfect normality is unattainable, the role of the manager is to reach maximum attainable position. It regulates the supply of forest products on sustainable basis as well as restoring the health and vitality of the forest.